Development and evaluation of Methocel K15M based Theophylline floating tablets - Sayeeda Tasneem Chowdhury, A H M Mohidul Kabir, Nashid Karim, Md. Shahid Sarwar, Md. Delowar Hossain, Md. Shohel Hossain, Mohammad Safiqul Islam (Journal of Applied Pharmaceutical Science, 2013)
The purpose of the investigation highlights the formulation and optimization of floating tablets containing theophylline as a model drug. Formulations were optimized for different concentrations of cetyl alcohol, citrc acid and methocel K15M by direct compression method. The dissolution study of the tablet matrices of 9 different formulations were carried out in 0.1N HCl as the medium (pH 1.3) for 8 hours using USP type II dissolution apparatus. It was observed the floating lag time for the tablet was 30 seconds and the total floating time was more than 8 hours. The drug release pattern was simulated in different kinetic orders such as Zero Order, First Order, Higuchi, and Korsmeyer release kinetic model. From the study, we observed that Higuchi release kinetics was predominant over other release kinetics and diffusion was the drug release mechanism from the matrices. Korsmeyer-Peppas release kinetics suggests that formulation F3, F4 and F9 followed Fickian type release mechanism whereas formulation F1, F2, F5, F6, F7 and F8 followed Non-Fickian type release mechanism. Thus, it is possible to design theophylline loaded Methocel K15M sustained release matrix tablets with desirable release characteristics by judicious and critical combination of Methocel K15M with other hydrophilic materials.
Keywords: Sustained release dosage form, floating tablet, theo